Microbiology of Cystic Fibrosis Airway Disease - Blanchard, Ana C.; Waters, Valerie J. (Seminars in Respiratory and Critical Care Medicine, 2019)
Although survival of individuals with cystic fibrosis (CF) has been continuously improving for the past 40 years, respiratory failure secondary to recurrent pulmonary infections remains the leading cause of mortality in this patient population. Certain pathogens such as Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus, and species of the Burkholderia cepacia complex continue to be associated with poorer clinical outcomes including accelerated lung function decline and increased mortality. In addition, other organisms such as anaerobes, viruses, and fungi are increasingly recognized as potential contributors to disease progression. Culture-independent molecular methods are also being used for diagnostic purposes and to examine the interaction of microorganisms in the CF airway. Given the importance of CF airway infections, ongoing initiatives to promote understanding of the epidemiology, clinical course, and treatment options for these infections are needed.
Keywords: cystic fibrosis; microbiology; bacteria; fungi; viruses; microbiome